Wouldn't it be great [compact disc] - Lynn, Loretta (Legacy Recordings, 2018)
Loretta Lynn's follow up to her Grammy nominated Full Circle mixes new compositions with newly imagined versions of her timeless classics, including Coal Miner's Daughter. It shows that her songwriting is as sharp as ever.